2020
DOI: 10.1080/07391102.2020.1779133
|View full text |Cite
|
Sign up to set email alerts
|

Targeting SARS-COV-2 non-structural protein 16: a virtual drug repurposing study

Abstract: Non-Structural Protein 16 (nsp-16), a viral RNA methyltransferase (MTase), is one of the highly viable targets for drug discovery of coronaviruses including SARS-CoV-2. In this study, drug discovery of SARS-CoV-2 nsp-16 has been performed by a virtual drug repurposing approach. First, drug shapebased screening (among FDA approved drugs) with a known template of MTase inhibitor, sinefungin was done and best compounds with high similarity scores were selected. In addition to the selected compounds, 4 nucleoside … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
50
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(51 citation statements)
references
References 75 publications
1
50
0
Order By: Relevance
“…The above observations strongly suggested that Nsp16-Nsp10 may be a crucial drug target for highly specific anti-coronavirus drugs in comparison to the viral MTase active site (Rosas-Lemus et al, 2020). Several interesting studies have already been done by considering Nsp16-Nsp10 as an effective drug target for SARS-CoV-2 inhibition (Cavasotto & Di Filippo, 2020;Culletta et al, 2020;Kadioglu et al, 2020;Kandwal & Fayne, 2020;Tazikeh-Lemeski et al, 2020).…”
Section: Introductionmentioning
confidence: 96%
“…The above observations strongly suggested that Nsp16-Nsp10 may be a crucial drug target for highly specific anti-coronavirus drugs in comparison to the viral MTase active site (Rosas-Lemus et al, 2020). Several interesting studies have already been done by considering Nsp16-Nsp10 as an effective drug target for SARS-CoV-2 inhibition (Cavasotto & Di Filippo, 2020;Culletta et al, 2020;Kadioglu et al, 2020;Kandwal & Fayne, 2020;Tazikeh-Lemeski et al, 2020).…”
Section: Introductionmentioning
confidence: 96%
“…Moreover, in silico approaches, including molecular dynamics (MD), have also been widely used to determine the conformational space of the investigated targets, ligands, and ligandtarget complexes, and thus better understand the dynamic behavior of ligand-target complexes Pinzi & Rastelli, 2019;Rajendran et al, 2018;Slater & Kontoyianni, 2019;Sled z & Caflisch, 2018). Very recently, a virtual screening approach was used to identify potential drugs to inhibit SARS-CoV-2 proteins, including surface spike glycoprotein, main protease, and nsp16 Panda et al, 2020;Tazikeh-Lemeski et al, 2020;Vijayan et al, 2020). For example, Bhardwaj et al reported the identification of bioactive molecules from tea plant as SARS-CoV-2 main protease inhibitors .…”
Section: Introductionmentioning
confidence: 99%
“…reported the identification of bioactive molecules from tea plant as SARS-CoV-2 main protease inhibitors (Bhardwaj et al., 2020 ). Molecular docking and virtual screening approaches also have been attempted to identify compounds targeting 2′-O-MTase of SARS-CoV-2 (Encinar & Menendez, 2020 ; Hijikata et al., 2020 ; Tazikeh-Lemeski et al., 2020 ; Vijayan et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Another study focused on using DBVS to determine the inhibitory activity of FDA approved drugs against nsp16. The results indicated the potential of anti-viral drugs (maraviroc and raltegravir) and an anti-inflammatory drug (prednisolone) to be effective drug candidates against nsp16 (Tazikeh-Lemeski et al, 2020 ). Another such study integrated a data-driven repositioning framework to predict effective drug candidates with in silico screening followed by wet-lab validation.…”
Section: Introductionmentioning
confidence: 99%